ACCOUNTING AND ANALYTICAL SUPPORT AND ECONOMIC CONTROL OF COMPANIES’ STAFF PAYMENT CALCULATIONS USING DIGITAL TECHNOLOGIES AND MANAGEMENT OF GRANT ACTIVITIES - Balaniuk , I. F.; Kuzmin , T. L.; Boichuk , T. R.; Smushak , M. V. (The actual problems of regional economy development, 2024)
The article is directed to the study of the main aspects of the application of digital technologies for accounting and economic control of payroll calculations of the company's personnel, including the analysis of the effectiveness of the use of digital tools, their impact on the productivity and efficiency of personnel management, the identification of advantages and possible limitations of their use in this context, as well as management of grant activities. The purpose of the article is to study the use of digital technologies for accounting and economic control of payments for enterprise personnel and grant activities. To achieve the goal, research methods are used in the article, namely: induction and deduction – to determine the main advantages and disadvantages of digital technologies for accounting and economic control of calculations for the remuneration of the company's personnel; system analysis – for the study of accounting and control processes in their relationship with the system of digital technologies; synthesis – to generalize various aspects of the study of digital technologies for accounting and economic control of the remuneration of the company's personnel; abstraction – to develop conclusions and proposals; graphic – for visualization of research results. The article determines that the analysis of accounts for grouping information by types and forms of remuneration helps to understand the structure of personnel costs, to identify trends in their strengthening or reduction, and to make informed management decisions. The main capabilities of software products designed for accounting and economic control of employee salary calculations are defined, namely: "Parus – salary", BAS "Salary and Personnel Management", "New accounting" with the "Salary" module, "Galaxy" : HR". The main advantages and disadvantages of using the above programs are highlighted. It is noted that one of the directions of the company's activity is the attraction and use of grant funds for the purchase and updating of new digital technologies that can significantly increase management efficiency. The scientific novelty of the study is the grouping and identification of the main capabilities, advantages and disadvantages of digital technologies for accounting and economic control, calculations of the remuneration of the company's personnel, grant activity, determination of their impact on the efficiency of resource management, as well as the identification of opportunities for their improvement and implementation in practice. The results of the scientific process can be used by enterprises during their activities to optimize the processes of accounting and economic control and management of grant activities.